2021
DOI: 10.1126/sciadv.abh0250
|View full text |Cite
|
Sign up to set email alerts
|

X-ray free-electron laser studies reveal correlated motion during isopenicillin N synthase catalysis

Abstract: Isopenicillin N synthase (IPNS) catalyzes the unique reaction of l--(-aminoadipoyl)-l-cysteinyl-d-valine (ACV) with dioxygen giving isopenicillin N (IPN), the precursor of all natural penicillins and cephalosporins. X-ray free-electron laser studies including time-resolved crystallography and emission spectroscopy reveal how reaction of IPNS:Fe(II):ACV with dioxygen to yield an Fe(III) superoxide causes differences in active site volume and unexpected conformational changes that propagate to structurally rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 74 publications
(116 reference statements)
2
25
0
Order By: Relevance
“… 22 , 23 Importantly, the ability of SCS residues to induce fast motions has been demonstrated by experimental work, including on a penicillin-forming oxidase, which is structurally and mechanistically related to the 2OG oxygenases. 24 26 Further, an SCS substitution of lysine (K241) to alanine in the 2OG-dependent JmjC KDM4A has been shown to ablate demethylation activity. 27 A computational study explored the effects of K241A, Y177A, and N290A variations in KDM4A and demonstrated that in these variants, the histone substrate (H3K4me3) adopts a nonproductive conformation; 28 these results are in agreement with experimental studies for K241A.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 22 , 23 Importantly, the ability of SCS residues to induce fast motions has been demonstrated by experimental work, including on a penicillin-forming oxidase, which is structurally and mechanistically related to the 2OG oxygenases. 24 26 Further, an SCS substitution of lysine (K241) to alanine in the 2OG-dependent JmjC KDM4A has been shown to ablate demethylation activity. 27 A computational study explored the effects of K241A, Y177A, and N290A variations in KDM4A and demonstrated that in these variants, the histone substrate (H3K4me3) adopts a nonproductive conformation; 28 these results are in agreement with experimental studies for K241A.…”
Section: Introductionmentioning
confidence: 99%
“… 39 , 40 However, identifying residues at LR from the active site relevant for catalysis remains challenging, and experimental approaches, e.g., employing X-ray free electron laser-based analyses to study correlated motions during specific steps in catalysis by oxygenases, are demanding and expensive. 26 , 41 Recent studies demonstrated that electrostatic perturbations could be a promising tool to modulate the rate and specificity of chemical reactions. 42 44 Computational methods thus have an important role in studying factors away from the active site that regulates the kinetics of individual steps in oxygenase catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). These data provide a real-time handle to monitor both oxidation state and electronic structure during Serial Femtosecond Crystallography [46,47]. The oxidized MCR data was compared against those of two water-soluble nickel(II) standards, [Ni (H2O)6] 2+ and [Ni(bpy)3] 2+ (bpy = 2,2 ′ -bipyridine), which were also collected in solution at room temperature at the XFEL using the DOT sample delivery system.…”
Section: Simultaneous Collection Of Ni Xes For the Mcrred1-silent Formmentioning
confidence: 99%
“…FH facilitates the synthesis of cysteine, which is the precursor for penicillin and cephalosporin synthesis. IPNS can catalyze the specific reaction of L-δ-(α-aminoadipoyl)-Lcysteinyl-D-valine with dioxygen giving isopenicillin-N, a precursor of cephalosporins and penicillins (Rabe et al, 2021). The significant abundance increase of these DAPs under dessication-stress is beneficial to the accumulation of penicillin and cephalosporin in A. fibrillifera.…”
Section: Antibiotics Involved In Dessication Tolerancementioning
confidence: 99%